Hubungan Pengendalian Intern dan Kompensasi dengan Kecurangan Akuntansi ( Studi pada BPR di Provinsi Lampung ) - Aminah AMINAH; Chindy Yolanda Faramitha (Jurnal Akuntansi dan Keuangan, 2016)
In this study used quantitative analysis method, which samples used were obtained from the questionnaire data (questionnaire). Method of quantitative analysis in general is a method that is more emphasis on the objective measurement of the social phenomena. To be able to perform measurements, every social phenomenon translated into several components of the problem, variables and indicators. Each variable is determined at the measurement by providing symbols figures vary according to the categories of information relating to these variables. Formulation of the problem in this research is "Is the internal control and compensation effect with accounting fraud?" The purpose of this study was to examine the empirical evidence of the effect of internal control and compensation for accounting fraud. This study uses Pearson correlation with data collection using questionnaires. The results of this study indicate that the influence of internal control of accounting fraud and do not significantly affect the compensation.